1969
DOI: 10.2134/agronj1969.00021962006100050033x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Minimum Tillage and Herbicide for Establishing Legumes in Kentucky Bluegrass (Poa pratensis L.) Swards1

Abstract: Factorial experiments were conducted for three successive years with plantings of alfalfa (Medicago sativa L.) made in spring, mid‐and late summer of each year. White clover (Trifolium repens L.) was sown only in spring. Tillage levels were none and strips tilled to a depth of 1.9 cm with widths of 0.6, 1.9 and 5.7 cm. Herbicide levels were none and paraquat, l:l‐dimethyl‐4, 4'dipyridylium dichloride, applied at 1.11 kg a.i./ha in bands of 5.1 and 10.2 cm over the seeded rows. Seeds were placed either on or be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

1974
1974
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 4 publications
(4 reference statements)
2
32
0
Order By: Relevance
“…Although these densities were similar to those regarded by Hay et al (1978) to give satisfactory red clover production, it is quite apparent that the red clover plants overdrilled in paraquat bands in this experiment remained too small to make an agronomically significant contribution to yield. The relative improvement of red clover yield brought about by overdrilling compared to oversowing, and the use of paraquat bands (Tables 1 and 2), are similar to findings of Taylor et al (1969) who found that overdrilling with paraquat sprayed in bands resulted in greater plant size and doubled the plant number compared with oversowing. However, the absolute yield response was not of practical significance especially when compared to the levels of red clover yield obtained with full cultivation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Although these densities were similar to those regarded by Hay et al (1978) to give satisfactory red clover production, it is quite apparent that the red clover plants overdrilled in paraquat bands in this experiment remained too small to make an agronomically significant contribution to yield. The relative improvement of red clover yield brought about by overdrilling compared to oversowing, and the use of paraquat bands (Tables 1 and 2), are similar to findings of Taylor et al (1969) who found that overdrilling with paraquat sprayed in bands resulted in greater plant size and doubled the plant number compared with oversowing. However, the absolute yield response was not of practical significance especially when compared to the levels of red clover yield obtained with full cultivation.…”
Section: Discussionsupporting
confidence: 81%
“…With limited supply of moisture in spring the development of overdrilled seedlings may be set back and result in poor establishment (Groya & Sheaffer 1981). It is under such adverse moisture conditions that the selection of a suitable directdrilling technique, including the coulter design, may greatly improve seedling survival and development (Taylor et al 1969;Baker 1976;Choudhary & Baker 1977).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of vegetation suppression needed for successful forage crop establishment is related to seedling vigor, botanical composition, and soil texture (Taylor et al 1969(Taylor et al , 1972 (Kunelius and Campbell 1986). Rayburn et al (1981) found that seeding legumes directly into a grass sod can produce yields comparable to conventional tilling.…”
mentioning
confidence: 99%
“…The degree of sod suppression required for forage legume establishment depends on the seedling vigor of the seeded legume species, the botanical composition of the sward, and the effects of edaphic and environmental conditions on sward and legume growth (Taylor et al 1969;Taylor et al 1912, Moshier and Penner 1978; Groya and Sheaffer 1981).…”
mentioning
confidence: 99%